The efficacy and the safety of eltrombopag in pediatric patients with severe aplastic anemia: a systematic review - Marrapodi, Maria Maddalena; Mascolo, Annamaria; Roberti, Domenico; Martino, Martina Di; Rafaniello, Concetta; Riccardi, Consiglia; Rossi, Francesca (Frontiers in Pediatrics, 2023)
Background: Acquired aplastic anemia (AAA) in pediatric patients is a rare disorder characterized by hypocellular bone marrow and pancytopenia. Eltrombopag, an oral thrombopoietin receptor agonist, provides a hematologic improvement in adults with severe aplastic anemia (SAA) refractory to immunosuppressive therapy (IST). The association of ELT and IST was approved by the US Food and Drug Administration (FDA) for adults and children 2 years of age as a first-line treatment for SAA. However, the effects of ELT on pediatric patients with SAA remain controversial and limited. Methods and findings: We conducted a systematic review of the most recent literature from Pubmed, Web of Science, and Embase, published up to December 20, 2022, in order to evaluate the available evidence on the efficacy and safety of ELT added to IST for the treatment of SAA in the pediatric population. Conclusion: Eltrombopag added to the IST has shown a good safety profile, without manifestations of excessive toxic effects, although not all the results obtained from our studies support the addition of ELT to the IST in the first-line treatment of children with SAA.